PERFORMANCE OF FREE-PISTON LINEAR GENERATOR BY USING COMPRESSED AIR - JAMAL, IZZAT AMIR ZAFRI (IRC, 2016)
A two-stroke of UTP High Pressure Free-Piston Linear Generator (FPLG) engine is invented as a new source of green power generation. A linear engine coupled to a linear alternator consists of permanent –magnet and stator assembly becomes a linear-generator. The piston-shaft assembly consists of two pistons and a shaft where one piston is connected to each end of the shaft and a linear alternator at the middle of the engine. FPLG has only one moving mechanism which is a connecting rod with two pistons at both ends. The working principle of expansion of compressed air in a two-stroke of dual piston engine is used to convert kinetic energy into electrical energy via electromagnetic induction. Electricity is generated straight from the moving piston-rod-assembly forced by the injection of compressed air. The expansion process of compressed air in the power stroke is examined by varying the parameters such as injection supply pressure, valve injection timing and air flowrate.